Quality Management of Pedagogical Research - Tararina, Larisa I.; Atayanz, Nelli G.; Timonin, Andrey I.; BuldakÐ¾va, Natalya V.; Petrova, Tatiana A.; Gunina, Elena V.; Osokina, Tatyana V.; Ishmuradova, Alfiya M. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the positioning of education as a public good and meaningful domain of personality. Socio-economic transformations of modern society affect different social institutions, including education, participating in the development of mechanisms for reproduction of social structure, the formation of socially and economically active individual, creating a competitive situation on the market of educational services and serving as a basis of human resources capital. It claims to improve the quality of educational research that has acquired an interdisciplinary character. The testing of the effectiveness of educational researches’ results is carried out during the experimental work. The purpose of the article is to reveal the contents of experience-experimental work as the subject of quality management of pedagogical research. The leading approaches to the study are system approach that allows identifying of the types and functions of the experimental work and to establish relationships among them, and technological approach that allows developing of a program of experimental work. The paper defines the principles, clarifies the types, identifies functions and describes program and theoretical methods of the experimental work. Also it proposes classification of innovations in the educational system. The paper submissions can be useful for managers and teachers of educational institutions; employees of the centers of advanced training and retraining of personnel in the selection and structuring of the content for the training of scientific and pedagogical staff. Keywords: the quality of pedagogical research, experimental work, education as a publically significant benefit. JEL Classifications: I21, I25, I28